2021
DOI: 10.1002/advs.202100640
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic SERS Enhancement in GaN‐Ag Hybrid System toward Label‐Free and Multiplexed Detection of Antibiotics in Aqueous Solutions

Abstract: Noble metal-based surface-enhanced Raman spectroscopy (SERS) has enabled the simple and efficient detection of trace-amount molecules via significant electromagnetic enhancements at hot spots. However, the small Raman cross-section of various analytes forces the use of a Raman reporter for specific surface functionalization, which is time-consuming and limited to low-molecular-weight analytes. To tackle these issues, a hybrid SERS substrate utilizing Ag as plasmonic structures and GaN as charge transfer enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 73 publications
1
24
0
Order By: Relevance
“…Surface plasmon resonance (SPR) has been extensively employed for light-harvesting and conversion . Gold (Au) is considered a very promising SPR host because it offers tunable plasmon resonances in visible-light frequencies and excellent stability under harsh catalytic conditions. The energy stored in the SPR excitation may dissipate both radiatively and nonradiatively.…”
mentioning
confidence: 99%
“…Surface plasmon resonance (SPR) has been extensively employed for light-harvesting and conversion . Gold (Au) is considered a very promising SPR host because it offers tunable plasmon resonances in visible-light frequencies and excellent stability under harsh catalytic conditions. The energy stored in the SPR excitation may dissipate both radiatively and nonradiatively.…”
mentioning
confidence: 99%
“…SERS is an efficient and universal analysis technology with unique molecular fingerprint information. Due to its rapid and nondestructive detection characteristics, SERS technology has been widely used in environmental monitoring, 9 food safety, 10,11 chemical analysis and other fields. 12–14 In general, the SERS enhancement mechanism mainly includes the electromagnetic enhancement mechanism (EM) and chemical enhancement mechanism (CM).…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Consequently, an effective way to enhance the sensitivity of SERS is to fully combine the EM and CM mechanisms before the design of the substrate. For example, Lee et al 11 proposed a GaN/Ag hybrid SERS substrate, which exhibits superior SERS sensitivity for the detection of rhodamine 6G. Yang et al 17 reported an Au/W 18 O 49 heterostructure to realize quantitative and qualitative double detection with SERS monitoring and fluorescence sensing.…”
Section: Introductionmentioning
confidence: 99%
“…Based on a simple nanofiber preparation technology, namely electrospinning, an electrospun pyroelectric-modulated BiFeO 3 layer combined with an electron/heat conduction layer of CNFs may be the optimal choice to fabricate an efficient light-induced pyroelectric layer. 21,22 In addition, Ag NWs are one of the most promising SERS substrates due to their peculiar geometry with a non-circular cross-section and sharp tips, which allows for the efficient enrichment of the local electromagnetic field. 23–25 Owing to the emergence of hot spots among uniformly dispersed Ag NWs on BiFeO 3 /carbon nanofiber surfaces, hybrid SERS substrates will exhibit excellent light absorption, outstanding stability and tunable electric fields.…”
Section: Introductionmentioning
confidence: 99%